Effect of Truvada lawsuit advertising on preexposure prophylaxis attitudes and decisions among sexual and gender minority youth and young adults at risk for HIV. (1st January 2021) - Serrano, Pedro A.; Daubert, Elizabeth; Munoz, Alejandro; Hosek, Sybil G.; French, Audrey L.
Abstract : Objective: In 2019, US advocates reported misleading language regarding the safety of TDF/FTC (Truvada) used by lawsuit advertisements against Gilead Sciences. We sought to ascertain the reach and effects of the advertisements on preexposure prophylaxis (PrEP) opinions and decisions in a cohort of youth and young adults at-risk for HIV. Design: An online survey was administered to participants enrolled in Keeping it LITE, a prospective US cohort study of ethnically diverse, sexually active, cisgender and transgender persons ages 13–37. Methods: Quantitative data were analyzed using descriptive and inferential analysis in SAS, and qualitative data via thematic analysis. Results: Survey response rate was 51.3% ( n  = 1485). Mean age at baseline was 24. Previous PrEP use was reported by 43% of respondents and 32.7% reported PrEP use in the past 6 months. Almost half (48.7%) were aware of the lawsuit. Most of these participants (81.3%) reported the advertisements did not impact their PrEP use, but 13.2% decided to not to begin a Truvada-based PrEP regimen and 5.5% decided to stop taking Truvada due to the advertisements claims. Predictors of changing PrEP behavior were lower education and no previous PrEP use. The qualitative analysis revealed the advertisements increased skepticism about safety and benefit of Truvada PrEP and led to greater distrust of the pharmaceutical industry. Conclusion: The advertisements reached a large, diverse US audience. Disturbingly, 18.7% of PrEP candidates who were aware of the lawsuit attributed not initiating or cessation of a Truvada-based PrEP regimen to exposure to the Truvada lawsuit advertisements.